Maqashid Al-shari’ah based composite index to measure the socio-economic level - Nihayatus Sa'adah; Dahruji Dahruji (Jurnal Inovasi Ekonomi, 2022)
This study aims to determine the socioeconomic level of Muslim craftsmen of woven sarongs with a composite index approach based on maqashid sharia in Jogodalu Village, Benjeng District, Gresik Regency. The sample in this study was 54 craftsmen using the formula of Issac and Michael. This study shows that the socioeconomic level of Muslim sarong weaving craftsmen is included in the high category because the calculation of the fifth composite index of maqashid sharia is more than 50%.